Herbal medicine used for the treatment of diarrhea and cough in Kampala city, Uganda - Walusansa, Abdul; Asiimwe, Savina; Ssenku, Jamilu E.; Anywar, Godwin; Namara, Milbert; Nakavuma, Jesca L.; Kakudidi, Esezah K. (Tropical Medicine and Health, 2022)
Globally, diarrheal and respiratory diseases are among the main causes of mortality and morbidity. In Uganda, cities are facing proliferation of trade in herbal medicines (HM), including those for diarrhea and/or cough. Information on the economic, and the ethnopharmacological aspects of these HM is scarce, deterring the sector from achieving optimal capacity to support national development. We profiled the anti-diarrhea and/or anti-cough HM, and the basic economic aspects of HM trade in Kampala city, to support ethnopharmacological knowledge conservation and strategic planning. Methods: A cross-sectional survey was conducted on 65 herbalists using semi-structured questionnaires. This was supplemented by an observational survey using a high-resolution digital camera. Data were collected following the guidelines for research on HM, established by Uganda National Drug Authority, and World Health organization. Results: Eighty-four plant species from 41 families were documented. Fabaceae and Myricaceae had the highest number of species (9, 10.7% each). Citrus limon (L.) Osbeck was the most commonly cited for cough, with a relative frequency of citation (RFC) of 1.00, and its relative medical importance was not significantly different from the other top 5 species except for Azadirachta indica A.Juss (RFC = 0.87). Entada abyssinica A. Rich (RFC = 0.97) was the most cited for diarrhea. Trees (34, 40.5%) were mostly used, and mainly harvested from wild habitats (55.2%) in 20 districts across Uganda. These HM were mainly sold as powders and concoctions, in markets, shops, pharmacies, and roadside or mobile stalls. The highest prices were Uganda Shillings (UGX) 48,000 ($13.15)/kg for Allium sativum L, and UGX 16,000 ($4.38)/kg for C. limon. All participants used HM trade as a sole source of basic needs; majority (60.0%) earned net monthly profit of UGX. 730,000 ($200) ≤ 1,460,000 ($400). The main hindrances to HM trade were the; disruptions caused by the COVID-19 pandemic (n = 65, 100%), and the scarcity of medicinal plants (58, 89.2%). Conclusion: There is a rich diversity of medicinal plant species traded in Kampala to treat diarrhea and cough. The HM trade significantly contributes to the livelihoods of the traders in Kampala, as well as the different actors along the HM value chain throughout the country
Keywords: Herbal medicine; Trade; Cough; Diarrhea; Herbalists